(untitled) (Journal of Economic Research & Business Administration, 2015)
Rational development of agrarian and industrial complex with forecasting of risks at increase in profi tableness, productivity of rational use of resources with the help of multi-criteria optimizing models. Considered control over sensitivity to changes multi-criteria problems for compromising decisions arising under the infl uence of external business factors. Defi nition of possibilities of comparative decisions by means of the software according to possibilities MS Excel. Research the purpose of research is multi-criteria analysis of projects of rational development by means of multi-purpose optimizing models in the conditions of market risks. Control over sensitivity to changes multi-criteria problems for compromising decisions arising under the infl uence of external business factors. Defi nition of possibilities of comparative decisions by means of the software according to possibilities MS Excel. Research the purpose of research is multi-criteria analysis of projects of rational development by means of multi-purpose optimizing models in the conditions of market risks. Control over sensitivity to changes multi-criteria problems for compromising decisions arising under the infl uence of external business factors. Defi nition of possibilities of comparative decisions by means of the software according to possibilities MS Excel.